INCREASING STUDENTS' READING INTEREST THROUGH GLENN DOMAN METHOD WITH THE ASSISTANCE OF MEDIA FLASHCARD - Ainun Safitri; Rika Wulandari; Kusnaningsih (maktab: Jurnal Pendidikan dan Teknologi, 2022)
The purpose of this study was to determine the increase in reading interest of class II students at Banyuajuh 2 Elementary School through the Glenn Doman method with the aid of flashcard media. This research is a class action research. The subjects of this study were teachers and students at Banyuajuh 2 Elementary School. Data collection techniques in this study used observation, interviews, questionnaires, and documentation. From the results of this research, in cycle I, the students' lack of interest in reading, the researcher decided to continue the research in cycle II. The results of the study showed an increase in students' interest in reading in each cycle. Evidenced by the results of teacher and student observations in the first cycle were 72% and 70%, respectively. This score increased in cycle II, namely 88% and 95% respectively. The results of this increase in reading interest can also be seen from the results of the student questionnaire which also increases in each cycle. In cycle I, the score from the student activity questionnaire showed a percentage of 63.92, then in cycle II it increased to 83.21. From the results of this study, it can be concluded that the use of the Glenn Doman Method assisted by flashcard media can increase students' reading interest in grade II Banyuajuh 2 Elementary School.